2017
DOI: 10.18203/2320-6012.ijrms20174913
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of insecticide treated nets against malaria among pregnant women in Southern Nigeria

Abstract: Malaria remains one of the most important causes of maternal and child morbidity and mortality in sub-Saharan African, despite the availability of effective intervention. Pregnant women are susceptible to symptomatic malaria due to the invasion of the placenta by Plasmodium. There are public health endeavours in promoting use of insecticide treated nets (ITNS), but there is dearth of data on effectiveness of such endeavour. This narrative review looks briefly at the historical background of use of ITNS against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…This finding is a little bit comparable with studies done in Uganda (66.8%) [38] and Ghana (66.1%) [21]. However, the result of this research is higher than studies done in Nigeria in 2012(39.1%), 2014(49.2%), and 2017 (49.6%) [22, 25, 26]. The possible explanation of the difference may due to time variation, sociodemographic difference, and study design difference.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This finding is a little bit comparable with studies done in Uganda (66.8%) [38] and Ghana (66.1%) [21]. However, the result of this research is higher than studies done in Nigeria in 2012(39.1%), 2014(49.2%), and 2017 (49.6%) [22, 25, 26]. The possible explanation of the difference may due to time variation, sociodemographic difference, and study design difference.…”
Section: Discussionsupporting
confidence: 84%
“…Even if the magnitude of malaria during pregnancy is high and there are different strategies to decrease the risk of malaria for vulnerable groups, many articles revealed that the use of ITNs by the pregnant woman in sub-Saharan countries including Ethiopia is very low [1526]. And this low utilization of ITNs by pregnant women is affected by education status, occupation, residence, ownership of television or radio, religion, ethnicity, age, and family monthly income [2737].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the association between income and malaria preventive action was reported, where higher income groups are two times more likely to practice than low-income groups [51]. Access to the intervention was infl uenced by household income [52]. Although ITN is suggested as a means of malaria reduction, communities with large families and low incomes are more aff ected by malaria disease [53].…”
Section: The Moderating Role Of Household Income On the Relationships Between Strategic Interventions And Malaria Controlmentioning
confidence: 99%
“…Likewise, the study revealed the association between income and practice of malaria preventive actions, where higher income groups are more likely to practice two times higher than low-income groups [51]. Besides, the report shows access to intervention is infl uenced by household income [52]. Moreover, malaria was reported as the leading cause of morbidity and mortality in low and middleincome countries [45,46].…”
Section: The Moderating Role Of Household Income On the Relationships Between Strategic Interventions And Malaria Controlmentioning
confidence: 99%